Protein content and electrophoretic profile of fat body and ovary extracts from workers of Melipona quadrifasciata anthidioides (Hymenoptera, Meliponini) - Oliveira, Vagner T. Paes de [UNESP]; Cruz-Landim, Carminda da [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2004)
Workers of Melipona quadrifasciata anthidioides (Lepeletier, 1836) develop their ovaries and lay eggs, therefore the production of vitellogenin is expected. In electrophoretic profiles only fat body extracts from nurse workers and ovary extracts from newly-emerged workers show protein with molecular mass similar to vitellogenin. However, an increase in the protein content was detected in forager fat body. This increase was attributed to storage of vitellogenin or other proteins in the previous phase and not discharged into the hemolymph or to an effect of the increased titre of juvenile hormone in this phase of worker life over the fat body functioning.
Keywords: Stingless bees; fat body; ovary; vitellogenin; oogenesis